Assessment of the Geomorphological Diversity of Komati Gorge, Mpumalanga Province, South Africa - Mukhodeni Mudau; Edmore Kori (Geoconservation Research)
The emerging broad science of geodiversity defined in terms of geomorphological diversity assesses geomorphological features of territory by comparing them in an extrinsic and intrinsic way. This paper uses SRTM (Shuttle Radar Topographic Mission) data and GIS (Geographical Information System) techniques to assess the geomorphological diversity of Komati Gorge, in Mpumalanga Province of South Africa. Factors used to assess geomorphological diversity are relative height, insolation, hydrography, geology, soil erodibility, ruggedness, slope position, and land use/land cover. Each factor was normalized to five classes by applying natural breaks, and all were weighted before overlaying. The weighting reveals that hydrography, ruggedness, relative heights, and geology carry more weight, respectively. Slope position, insolation, land use/land cover, and soil carry the least weight in that order. The final geomorphodiversity map reveals that the south-western parts of Komati Gorge have medium to very high geomorphological diversity. The north-eastern parts have low to medium geomorphological diversity. This indicates that factor-specific research can add more information to geomorphodiversity research and education.